(untitled) (Research, Society and Development, 2022)
Studies report greater exposure to the risk of accidents within the veterinary environment. In this sense, the objective of this study was to investigate and compare the occurrence of occupational accidents for administrative technicians in education, teachers and outsourced workers at a university veterinary hospital in southern Brazil. For this, we used a questionnaire formulated by the authors with 31 questions, sent by electronic address to 55 administrative technicians in education, 12 outsourced workers and 25 teachers assigned to the study site. Our results demonstrate that knowledge of specific regulations for the health environment was greater in the group of workers who received training. The needle disposal behavior is related to accident claims involving sharps for administrative technicians. Accidents that directly involved patients, accidents involving biological secretions and risk of exposure to ionizing radiation were the ones with the highest percentage for statements among employees, although there were no statements among outsourced workers. Physical or verbal aggression was reported in all groups, as well as the search for specialized care to treat discomforts or injuries related to work at the veterinary hospital. The lack of knowledge about the conduct in carrying out accident records was the most cited reason for the lack of it.